Reconfigurations of Islamic authority in Malaysia: state control of Islam and the role of the Ulama - Shiozaki, Yuki; Kushimoto, Hiroko (Brill, 2014)
The role and status of religious authority needs to be read into Malaysian political history over the past fifty years. During this period as the Malaysian state constructed its national identity and plotted its policy course, the role of Islam and religious leaders became an important point of debate. It is within this context that this article considers the independence and autonomy of Malaysian Muslim religious leaders. Traditional religious authority in Malaysia finds its underpinnings largely in the institutions of Islamic learning locally known as pondoks, which are a community of students of Islam under the directions of a religious leader, ulama (also often known as a Tok Guru). However as the state consolidated their control over these religious leaders whom were co-opted into the state apparatus, by employment and education at state universities, their social significance has been destabilized. In the wake of this compromised sociopolitical and religious position alternative sources of authoritative Islamic teachings have emerged in recent years such as the Tablighi Jama.at discussed in this article